2006
DOI: 10.1111/j.1365-2222.2006.02599.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular fingerprinting of the intestinal microbiota of infants in whom atopic eczema was or was not developing

Abstract: SummaryBackground The rise in atopic diseases has been linked to disturbances in the intestinal microbiota composition. Objective The purpose of this study was to investigate the intestinal microbiota composition in infants in whom atopic (IgE-associated) eczema was or was not developing, using a molecular fingerprinting technique. Methods Within a prospective birth cohort study, fecal samples have been collected at the infant's age of 1 month. Within the context of this cohort, we conducted a nested case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
2
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 37 publications
6
103
2
7
Order By: Relevance
“…During early infancy, multiple factors have been identified as potentially influencing the composition of the intestinal microbiota (24,25,26,28). As expected, in our study parameters that influenced dominant bacterial composition were age of the infants, type of feeding, and term of birth.…”
Section: Discussionsupporting
confidence: 66%
“…During early infancy, multiple factors have been identified as potentially influencing the composition of the intestinal microbiota (24,25,26,28). As expected, in our study parameters that influenced dominant bacterial composition were age of the infants, type of feeding, and term of birth.…”
Section: Discussionsupporting
confidence: 66%
“…However, the findings of one study are discordant (Sepp et al, 2005) with none of the 5-year-old children with atopic dermatitis and only one child with bronchial asthma colonized with bifidobacteria. Besides, low levels of bifidobacterial colonization have been observed in infants suffering from atopic dermatitis (Kirjavainen et al, 2001;Watanabe et al, 2003;Mah et al, 2006) and in infants suffering from atopic dermatitis and wheezing; note that these results have been contradicted by studies comparing healthy subjects with wheezing infants without other symptoms (Murray et al, 2005) and with patients suffering from both atopic dermatitis and food allergy (Penders et al, 2006a).…”
Section: Microbiota and Allergymentioning
confidence: 59%
“…Indeed, it seems unlikely that all members of this genus exert the same effects on the human immune system (Penders et al, 2007). Children not developing allergy before age 2 years have been shown to be more frequently colonized with bifidobacteria than children developing allergy (Bjorksten et al, 2001), but this decreased prevalence of Bifidobacterium in children suffering allergies was not confirmed in all studies (Songjinda et al, 2007;Penders et al, 2006a;Adlerberth et al, 2007). Differences in patterns of colonization by bifidobacteria species have also been observed but no clear consensus exists.…”
Section: Does Dysbiosis Precede Allergic Symptoms? Prospective Studiesmentioning
confidence: 94%
“…Kalliomaki et al reported that atopic children had more clostridia at 3 wk of age (33). Furthermore, Escherichia coli and Clostridium difficile were reportedly associated with infants who developed AD (34,35). In our present study, preliminary analysis of 16S rRNA gene clone libraries generated from cecal DNA samples in NC/Nga mice showed that the phyla Firmicutes and Proteobacteria were the most abundant taxonomic groups in both FOS(Ϫ) and FOS(ϩ) groups and that mice fed FOS(ϩ) had more Firmicutes and less Proteobacteria as compared to mice fed FOS(Ϫ) (data not shown).…”
Section: Resultsmentioning
confidence: 99%